Proceedings of the First International Workshop on Technology and Policy for Accessing Spectrum - TAPAS '06 2006
DOI: 10.1145/1234388.1234389
|View full text |Cite
|
Sign up to set email alerts
|

Chicago spectrum occupancy measurements & analysis and a long-term studies proposal

Abstract: This paper describes spectrum occupancy measurements performed in Chicago, IL in November 2005 and proposes long-term studies in multiple locations. The Chicago project consisted of deploying a high dynamic range spectrum measurement system, a data collection and processing system and conducting spectrum occupancy measurements in all bands between 30 MHz and 3,000 MHz (see Figure 1). These measurements were taken over a two-day period and are added to an existing body of data compiled in other cities and reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
205
0
14

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 380 publications
(223 citation statements)
references
References 0 publications
4
205
0
14
Order By: Relevance
“…Nonetheless, extensive studies (e.g., FCC (2002), McHenry et al (2006)) have shown that many spectrum bands are heavily under-utilized due to the significant variations in spectrum occupying time and space. This suggests that the traditional static licensing approach, i.e., granting exclusive spectrum usage right to a single commercial or government department over a long time and in a large area, is no longer efficient or suitable for future wireless networks.…”
Section: Background and Motivationsmentioning
confidence: 99%
“…Nonetheless, extensive studies (e.g., FCC (2002), McHenry et al (2006)) have shown that many spectrum bands are heavily under-utilized due to the significant variations in spectrum occupying time and space. This suggests that the traditional static licensing approach, i.e., granting exclusive spectrum usage right to a single commercial or government department over a long time and in a large area, is no longer efficient or suitable for future wireless networks.…”
Section: Background and Motivationsmentioning
confidence: 99%
“…Lemma 2: In simple allocation algorithm, if any buyer i is allocated by bidding b 1 , then it will also be allocated if it bids b 2 , where b 2 > b 1 .…”
Section: A a Simple Truthful Auctionmentioning
confidence: 99%
“…Traditionally, to eliminate the interference between different wireless communication pairs, radio spectrum is divided into a set of disjoint sub-bands and authorized to licensed users in a static fashion. With this kind of spectrum allocation approach, each licensed user has exclusive right for the allocated spectrum, thus always leading to lower spectrum utilization [1]. In recent years, with the rapid deployment of wireless facilities as well as the explosive growth of novel wireless services, the demand for radio spectrum is constantly increasing.…”
Section: Introductionmentioning
confidence: 99%
“…Spectrum measurements are essential for a proper understanding of real spectrum usage and can support regulatory organisms in taking actions to improve the use of the precious spectral resources. A good example of this is the important number of recent spectrum measurement campaigns that have been carried out all over the world in order to determine the degree to which allocated spectrum bands are used in real wireless communication systems [2][3][4][5][6][7][8][9][10][11][12][13][14]. Measurement results have demonstrated that spectrum is currently underutilized as a result of the owned spectrum allocation policy in use since the early days of modern radio communications.…”
Section: Introductionmentioning
confidence: 99%